The fundamental cause of ethnic conflict : a comparative analysis of the South Thailand insurgency and West Papua conflict - Nordin, Hana (2017)
The South Thailand insurgency and West Papua conflict are two protracted ethnic conflicts that are still ongoing today. This paper aims to undertake a detailed comparative analysis of these two conflicts in order to identify why they remain unresolvable. Its objective is to identify whether they share a common cause or are products of entirely different causes. The identification of their causes will then allow for an evaluation of existing measures in order to access their suitability. The wider aim is to discover whether there could possibly be an encompassing cause and thus a corresponding solution to ethnic conflicts that could be identified, potentially preventing future ethnic conflicts.